Strategy Leadership in School Development: A Case Study of SDN 4 Kaliaman, Jepara - Kusmiati Kusmiati; Yovitha Yuliejantiningsih; Muhammad Prayito (Journal of Educational Sciences, 2026)
School development requires strategic leadership to ensure continuous improvement in educational quality and sustainability. However, many elementary schools still face challenges related to instructional quality, teacher capacity, and resource management. Therefore, this study aims to analyze the leadership strategies implemented by the principal in developing SDN 4 Kaliaman, Kembang Subdistrict, Jepara Regency. This research employed a qualitative case study approach, with data collected through observations, in-depth interviews, and documentation. The findings reveal that the principal implemented strategic leadership through participative school planning, teacher empowerment via continuous professional development, integration of technology in learning, and collaboration with parents and the local community. In addition, effective infrastructure development and efficient budget management supported the successful implementation of school programs. The study concludes that strategic leadership characterized by participatory planning, teacher capacity building, and optimal resource utilization plays a crucial role in fostering a conducive learning environment and supporting sustainable school development.